IBPGR annual report 1983 - International Board for Plant Genetic Resources (1984)
This report highlights the immediate impact of IBPGR's work by looking at a significant achievement in each of the strategic areas that the Institute pursues. Short introductions to each section illustrate the breadth of IBPGR's research work and the geographical dispersion of its area of operation. The report also contains information for the year 1983 on financial status, Board of Trustees and management team.